An Appraisal of the Forest Policy in Orissa - Sahu, N. C.; Das, B. (Indian Forester, 1979)
Forest policy in Orissa, as a matter of fact In India, has a long, ancestry, Sporadic attempts on the part of the native and British rulers to protect and exploit the forests form the ingredients of the present forest policy. Under the impact of planning forest policy exhibit new dimeonsions. Growth, stability Environmental and recreational aspects of forests and wild life protection, etc, form different Important facets of the new forest policy, Some gaps, however, have been identified in the structure of the forest policy pursued in Orissa It has been felt that the forest policy has not been looked at in depth as developmental imperatives warrant.